Investigating the effects of split injection with different injection patterns on diesel spray mixing - Naruemon, Intarat; Liu, Long; Mei, Qihao; Wu, Yue; Ma, Xiuzhen; Nishida, Keiya (Frontiers in Energy Research, 2023)
In recent studies, it has been established improvement in injection rate results in improved mixing and combustion efficiency, as well as reduced pollutant emissions. Varying injection rates have been observed to find out the optimization injection rate. In this study, the split injection with different injection rates was used as the flexible injection to investigate the diesel spray mixing efficiency. The Large Eddy Simulation (LES) was used to investigate the complex diesel mixing processes of unsteady turbulence. The split injection was combined with different fuel injection rates to approximate the ramping down rate shape. The simulation results of flexible injection rates showed the formation of a highly unstable aerosol vapor structure with the turbulence structure that produces the vortex in the spray area. The powerful injection rates provide a very strong spray turbulence structure and vortex formation. Backflow and vortex are evident when setup the dwell time of injection. The flexible injection rates have a huge influence on the mixing efficiency of the fuel spray. Basic mixing efficiency predictions revealed that the dwell time of split injection and inverse injection pressure affect the turbulence structure. Another the initial pressure of the injection rate has a significant impact on evaporation and mixing efficiency, even using the same fuel quantity and same condition. The double-rectangular split injection has a slight effect on the spray radial extension, and the spray area grows rapidly while the equivalence ratio is low. The double-drop split injection with a high-pressure difference has a great influence on the spray radial extension and the spray length. Additionally, higher injection pressure results in lower equivalence ratios and more efficient mixing.